Sesamin Enhances Nrf2-Mediated Protective Defense against Oxidative Stress and Inflammation in Colitis via AKT and ERK Activation. (26th August 2019) - Bai, Xupeng; Gou, Xiaoli; Cai, Peiheng; Xu, Chuncao; Cao, Lin; Zhao, Zhongxiang; Huang, Min; Jin, Jing
Abstract : Ulcerative colitis (UC) is a major form of inflammatory bowel disease (IBD) with high incidence and prevalence in many countries. Patients with UC usually suffer from a lifetime of debilitating physical symptoms. Therefore, developing effective therapeutic strategy that can manage this disease better and improve patients' life quality is in urgent need. Sesamin (SSM) is a lignan derived from sesame seeds. In this study, the protective effect of SSM against UC and the underlying mechanism were investigated in vitro and in vivo . Our data showed that SSM protected Caco-2 cells from H2 O2 -induced oxidative stress injury via GSH-mediated scavenging of reactive oxygen species (ROS). Dual luciferase reporter assay showed that the transcriptional activity of nuclear factor erythroid-related factor 2 (Nrf2) was significantly increased by SSM, and the ability of SSM to activate Nrf2-targeted genes was further confirmed in Caco-2 cells using western blot and quantitative real-time PCR (qRT-PCR). In contrast, Nrf2 knockdown abolished the protective effect of SSM. Additionally, we found that SSM also activated advanced protein kinase B (AKT) and extracellular signal-regulated kinase (ERK) in Caco-2 cells, while either AKT or ERK inhibition can prevent SSM-mediated nuclear translocation of Nrf2. Furthermore, SSM displayed a better protective effect against dextran sulfate sodium- (DSS-) induced UC compared with 5-aminosalicylic acid (5-ASA) in C57BL/6 mice. The enhanced Nrf2 signaling and activated AKT/ERK were also observed in the colon of mice after SSM administration. These results first demonstrate the protective effect of SSM against UC and indicate that the effect is associated with AKT/ERK activation and subsequent Nrf2 signaling enhancement. This study provides a new insight into the medicinal value of SSM and proposes it as a new natural nutrition for better managing the symptoms of UC.